MEDIASI DAYA TARIK FASHION DALAM HUBUNGAN KEINOVASIAN PRODUK DENGAN KINERJA PEMASARAN - Hendar Hendar (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2019)
This paper aims to investigate and examine the role of fashion attractiveness in mediating therelationship between product innovation (uniqueness and novelty) and marketing performance.A total of 229 small businesses in Indonesia were selected to be tested for regressionalrelationships of the four constructs. This study finds a positive influence of product novelty anduniqueness on fashion attractiveness, yet it does not affect marketing performance. Mediationanalysis shows that fashion attractiveness plays an important role in bridging the relationshipof product novelty and product uniqueness on marketing performance. Through an in-depthexamination of a variety of literature about dynamic capabilities, entrepreneurial marketing,and company performance, this paper offers a unique analysis of the correlation of productnovelty and product uniqueness on fashion attractiveness as well as its impact on marketingperformance in the small-scale fashion industry. Conceptual discussion and empirical result ofthe study extend previous researches on the culture of product innovation in small businesses.Keywords: Keinovasian Produk, Kebaruan Produk, Keunikan Produk, Day Tarik Fashion,Kinerja Pemasaran